2019
DOI: 10.1182/bloodadvances.2018028241
|View full text |Cite
|
Sign up to set email alerts
|

Burden and impact of multifactorial geriatric syndromes in allogeneic hematopoietic cell transplantation for older adults

Abstract: Multifactorial geriatric syndromes are highly prevalent in older patients with cancer. Because an increasing number of older patients undergo allogeneic hematopoietic stem cell transplantation (allo-HCT), we examined the incidence and impact of transplant-related geriatric syndromes using our institutional database and electronic medical records. We identified 527 patients age 60 years or older who had undergone first allo-HCT from 2001 to 2016 for hematologic malignancies. From the initiation of conditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…second, the heterogeneity in diagnosis, donor type especially a small percentage of haploidentical donor, transplant platforms, and post-transplant care may introduce selection biases. Third, in addition to pre-transplant risk factors, allo-HCT itself may introduce additional risk factors for survival such as graftversus-host disease and geriatric syndromes [27].Finally, this is a single institutional study which may not be applicable to other settings. We expect that the upcoming Blood and Marrow Transplant Clinical Trials Network (BMT CTN 1704) CHARM study will help address many of these issues ().…”
Section: Discussionmentioning
confidence: 99%
“…second, the heterogeneity in diagnosis, donor type especially a small percentage of haploidentical donor, transplant platforms, and post-transplant care may introduce selection biases. Third, in addition to pre-transplant risk factors, allo-HCT itself may introduce additional risk factors for survival such as graftversus-host disease and geriatric syndromes [27].Finally, this is a single institutional study which may not be applicable to other settings. We expect that the upcoming Blood and Marrow Transplant Clinical Trials Network (BMT CTN 1704) CHARM study will help address many of these issues ().…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, cognitive impairment is an established risk factor for postoperative delirium 33 and thus may contribute to delirium or falls; these complications have been shown to be associated with inferior NRM and OS after alloHCT. 34 We hypothesized that functional impairment as measured by GA would independently predict worse outcome. Surprisingly, the study did not replicate prior findings of the adverse influence of IADL impairment observed in most prior single-center studies, 12,14,15 although not all.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to higher rates of nonrelapse mortality among older adults, geriatric syndromes such as falls and delirium further complicate alloHCT. 20 Nonolder adult alloHCT engenders loss of function even 3 months after HCT, which may take 1 year to normalize in survivors. 21,22 Restrictive eligibility criteria (e.g., age younger than 70, low comorbidity) are understandable to attenuate rates of complications; yet these restrictions preclude HCT for older…”
Section: Optimization For Hematopoietic Cell Transplantationmentioning
confidence: 99%